INSTRUCTIONAL STRATEGIES IN BILINGUAL CLASSROOMS: A CLASSROOM OBSERVATION STUDY AT XIKOU BILINGUAL ELEMENTARY SCHOOL TAIWAN - Yofrina Octika (CV. ADIBA ASIHA AMIRA, 2024)
A classroom observation study at Xikou Bilingual Elementary School in Taiwan explored the instructional strategies applied in bilingual classes. The research findings highlight three key aspects of effective teaching in a bilingual classroom: the balanced use of Mandarin and English, the incorporation of media and games, and a persuasive student-centered approach. Observing the instructional strategies in bilingual classrooms offers insights into how teachers use certain approaches and media to support the students’ learning process. The primary data collection methods for this study are classroom observations and teacher brief interviews which provide rich, contextualized data about how bilingual education is practiced in the classroom. It was found that the teacher effectively balances both languages, facilitating language acquisition while maintaining clarity in instruction. Multimedia tools such as videos and interactive games are used to engage students, enhance understanding, and promote active participation in lessons. The teacher also adopts a persuasive and supportive teaching style, motivating students and fostering a positive classroom environment. Through the observation, it is recommended to emphasize the importance of end-of-lesson reflection sessions in enhancing student engagement and retention. By allowing students 3-5 minutes at the end of each lesson to reflect on key learnings, challenges, or interesting aspects, the teacher encourages self-awareness and deeper learning. This reflective practice, whether through individual journaling or group discussions, provides valuable insights for both teachers and students, ultimately improving the overall learning experience.